Radio Transients in the Era of Multi-Messenger Astrophysics: Workshop 1. Issue Volume 14:Issue S339(2018) (November 2017) - Anderson, G. E.; Stappers, B. W.; Andreoni, I.; Caleb, M.; Coppejans, D.; Corbel, S.; Fender, R. P.; Giroletti, M.; Graham, M. L.; Sokolovsky, K. V.; Woudt, P. A.
Abstract: Radio emission from astrophysical transients allows us to derive calorimetry of kinetic feedback and detailed imaging in ways that are not possible at other wavelengths, and as such it forms an important part of the multi-messenger follow-ups of these events. The field is burgeoning, with a renaissance of interest in accretion, stellar explosions and jetted supernovæ, alongside newer classes of phenomena such as fast radio bursts and tidal disruption events. The purpose of this workshop was to discuss the infrastructure and techniques for detecting, identifying and probing radio transients, with a particular focus on how best to exploit transient alerts from multi-messenger facilities. We examined the type of transient alerts those facilities will broadcast, and methods for following them up, such as rapid-response triggering and shadowing. In break-out groups, participants chose a science question related to a particular radio transient type or class and discussed whether the planned transient strategies and observing techniques on the Square Kilometre Array will be adequate to address the particular question. The classes they chose included fast radio bursts, supernovæ, cataclysmic variable and unknown transients. Any proposed adaptation or suggestion was relayed to a panel of experts for further discussion. The second part of the workshop concentrated on the application of long baseline interferometry for detecting and measuring radio transients.